Assessing discards in an illegal small-scale fishery using fisher-led reporting - Tania Mendo; Jaime Mendo; Janneke Ransijn; Iván Gómez; Patricia Gil‐Kodaka; Judy Ann H. Fernandez; Ruggeri Delgado; Alejandra Travezaño; Ruggeri Arroyo; Karla Loza; P. McCann; Sean A. Crowe; et al. (My University, 2022)
About a third of all marine fish in the world are caught in Small-Scale Fisheries (SSF). SSF are increasingly recognised as essential for food security and livelihoods for vulnerable and economically fragile communities globally. Although individual SSF vessels are usually perceived as having little impact on the ecosystem, the cumulative impact of gear type and number of vessels may be substantial. Bottom trawling is a common fishing method that can greatly influence the marine ecosystem by damaging the seafloor and generating high levels of discards. However, appropriate sampling coverage using on-board observer programmes to collect these data from SSF are rare, as they are expensive and pose logistical constraints. A mobile App was used to assess whether self-reporting by fishers could provide reliable fine-scale information on fishing effort and discards over time in an illegal shrimp trawling fishery in northern Peru. Maps depicting the spatial distribution of trawling effort and the proportion of discards from observers and fishers were compared using the Similarity in Means (SIM) Index, which ranges from 0 when spatial patterns differ completely to 1 when spatial patterns are very similar. High levels of agreement between spatio-temporal patterns of effort (SIM Index = 0.81) and discards (0.96) were found between fisher and observer maps. Moreover, far greater spatial coverage was accomplished by fishers, suggesting that self-reporting via an App represents a useful approach to collect reliable fisheries data as an initial step for effective monitoring and management of these fisheries. Supplementary Information: The online version contains supplementary material available at 10.1007/s11160-022-09708-9.
Keywords: Discards; Biology; Fishery; Scale (ratio); Fishing; Physics; Quantum mechanics; Discards; Biology; Fishery; Scale (ratio); Fishing; Physical Sciences Environmental Science Global and Planetary Change Marine and fisheries research; Physical Sciences Environmental Science Ecology Coral and Marine Ecosystems Studies; Physical Sciences Environmental Science Global and Planetary Change Marine Bivalve and Aquaculture Studies